2008
DOI: 10.1007/s11172-008-0232-3
|View full text |Cite
|
Sign up to set email alerts
|

Pyrano[4,3-d]pyrimidinium salts

Abstract: Reactions of 5 aryl and 5,7 diaryl 1,3 dimethyl 2,4 dioxopyrano[4,3 d]pyrimidinium salts with hydrazine were studied. In the former case, the reaction products were the 6 amino 1,3 dimethyl 2,4 dioxopyrido[4,3 d]pyrimidinium salts. 5,7 Diarylpyrano[4,3 d]pyrimidinium salts were transformed into either the corresponding pyridinium salts or 1H pyrimido [5,4 d][1,2]diazepine 2,4(3H,9H) diones, depending on the hydrazine concentration and the reaction time. Key words: pyrano[4,3 d]pyrimidinium salts, recyclization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…1 H NMR spectra were recorded on a Bruker Avance DPX 250 spectrometer. TLC was performed on aluminium oxide (Reaktiv Ltd.) with CHCl 3 as an eluent.…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR spectra were recorded on a Bruker Avance DPX 250 spectrometer. TLC was performed on aluminium oxide (Reaktiv Ltd.) with CHCl 3 as an eluent.…”
Section: Methodsmentioning
confidence: 99%
“…Bromides 1 were synthesized according to the proce dures described earlier. 2 6 (2 Aryl 2 oxoethyl) 1,3 dimethyl 5 [phenyl(phenylhydr azono)methyl]pyrimidine 2,4(1H,3H) diones 4 (general proce dure). A suspension of salt 1 (0.5 mmol), phenylhydrazine (0.054 mL, 59.4 mg, 0.55 mmol), and triethylamine (0.077 mL, 55.6 mg, 0.55 mmol) in AcOH (2 mL) was stirred for 1 h at 20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier, 2 we have reported that 5,7 diaryl 1,3 dimeth yl 2,4 dioxo 1H,3H pyrano [4,3 d]pyrimidinium brom ides 1 upon a short time heating with equimolar amount of hydrazine undergo recyclization to 1H pyrimido [5,4 d] [1,2]diazepine 2,4(3H,9H) dione hydrobromides 2. At the same time, compounds 1 and 2 upon treatment with ex cess hydrazine for 30 min are transformed to 6 amino 1,3 dimethyl 2,4 dioxo 1H,3H pyrido [4,3 d]pyrimidin ium salts 3 (Scheme 1).…”
mentioning
confidence: 99%
“…Although the preparation and studies about the pharmacological activities of pyrido[2,3- d ]pyrimidines and pyrido[3,2- d ]pyrimidines have been carried out in detail, construction of pyrido[4,3- d ]pyrimidines is a relatively less studied area. Most of the reported procedures for the synthesis of the pyrido[4,3- d ]pyrimidine unit suffer from the limitation of multistep synthesis, requirement of catalyst or additive, inert atmosphere, or stringent reaction conditions . Herdewijn et al have reported the synthesis of pyrido[4,3- d ]pyrimidines from 4,6-diaminonicotinamide but required long reaction time to obtain moderate to good yield of the product.…”
mentioning
confidence: 99%